Outcome of neoadjuvant chemotherapy in locally advanced breast cancer: A tertiary care center experience (Bangladesh Medical Journal, 2017)
Breast cancer is the most common cancer among Bangladeshi women. Almost all present with palpable lump and 40% of them are with locally advanced breast cancer. Neoadjuvant chemotherapy is the standard choice of treatment for the patients.This prospective study was done involving 220 newly diagnosed locally advanced breast cancer (LABC) patients from January 2010 to December 2014 in the National Institute of Cancer Research & Hospital (NICRH), Mohakhali, Dhaka to observe the clinical and pathological response of locally advanced breast cancer after four cycles of chemotherapy and surgery. Chemotherapy schedule with Cyclophosphamide 600mg/m2 and Doxorubicine 60mg/m2 (AC) was prescribed and carried out three weekly for four cycles. Primary tumor size and axillary nodal size was measured and compared with the previous record. After three weeks of chemotherapy the patients undergone mastectomy and axillary dissection. Histopathology was done to see the pathological response of primary tumor and axillary node. Other biological marker such as estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth receptor (HER-2) were done. After four cycles of chemotherapy with AC, 194 patients (88%) responded clinically, 29 patients (13%) showed complete clinical response (cCr) and 165 patients (75%) partial response (pCr). Surgical specimen showed complete pathological response (cPr) in 22 patients (10%). Neoadjuvant chemotherapy with AC is the standard chemotherapy schedule for locally advanced breast cancer and radical surgery was possible in 75% of the patients.Bangladesh Med J. 2016 Sep; 45 (3): 141-146